Insurance Sector in Indian Economy - M. Abbas Malik (AG Volumes, 2022)
In the past several years, the insurance industry in India has grown rapidly. Here, we look at the insurance industry in India from the beginning to the present, and chart its progress. Some of the critical problems in today’s business have been uncovered through our investigation. Low penetration and density rates; “lack of investment” in insurance products; the dominance of government insurers; and the degradation of those businesses’ financial health are some of the challenges mentioned in the study on the insurance industry. The growth of India’s economy depends on the country’s ability to absorb shocks; hence the creation of an insurance market is essential.